Changes in bank leverage: Evidence from US bank holding companies - Martin D. O'Brien; Karl Whelan (University College Dublin, UCD School of Economics, 2014)
This paper examines how banks respond to shocks to their equity. If banks react to equity shocks by more than proportionately adjusting liabilities, then this will tend to generate a positive correlation between asset growth and leverage growth. However, we show that in the presence of changes in liabilities that are uncorrelated with shocks to equity, a positive correlation of this sort can occur without banks adjusting to equity shocks by more than proportionately adjusting liabilities. The paper uses data from US bank holding companies to estimate an empirical model of bank balance sheet adjustment. We identify shocks to equity as well as orthogonal shocks to bank liabilities and show that both equity and liabilities tend to adjust to move leverage towards target ratios. We also show that banks allow leverage ratios to fall in response to positive equity shocks, though this pattern is weaker for large banks, which are more active in adjusting liabilities after these shocks. We show how this explains why large banks have lower correlations between asset growth and leverage growth.
Keywords: 330